Socioeconomic Feasibility of Waste-to-Energy Facilities: A Case Study in South DKI Jakarta - Rizal Riyadi; Tjahjo Tri Hartono; Mas Davino Sayaza (Universitas Ibn Khaldun Bogor, 2024)
The socioeconomic feasibility of Waste-to-Energy (WtE) facilities is analyzed through a case study in South Jakarta, emphasizing its potential as a sustainable urban waste management solution. This study evaluates the comparative costs and benefits of implementing an Intermediate Waste Treatment Facility (ITF) in three prospective locations: Sukapura (North Jakarta), Pesanggrahan, and Petukangan Selatan (South Jakarta). Results highlight Sukapura’s strategic advantage due to its industrial zoning, resulting in lower residential density, reduced social resistance, and minimized environmental costs. By contrast, higher costs are associated with South Jakarta sites due to greater population densities, leading to amplified pollution impacts. Key findings reveal that WtE facilities generate significant environmental and economic benefits, including reduced greenhouse gas emissions, improved air and water quality, job creation, and regional budget efficiencies. The integration of circular economy principles, such as waste reduction and resource efficiency, further underscores the importance of sustainable waste management strategies. However, successful WtE implementation requires careful alignment with land-use planning and community engagement to address socio-environmental challenges effectively. This study offers valuable insights for policymakers and urban planners, proposing that strategic site selection and adaptive approaches are critical for achieving long-term sustainability in waste management.